Experimental Actinobacillus pleuropneumoniae infection in piglets with different types and levels of specific protection: immunophenotypic analysis of lymphocyte subsets in the circulation and respiratory mucosal lymphoid tissue - Faldyna, M; Nechvatalova, K; Sinkora, J; Knotigova, P; Leva, L; Krejci, J; Toman, M (Veterinary immunology and immunopathology, 2005)
Actinobacillus pleuropneumoniae (APP) infection in piglets results in severe and fatal fibrinous hemorrhagic necrotizing pneumoniae. The aim of our study was to analyze changes in lymphocyte subset distribution in peripheral blood, bronchoalveolar lavage fluid (BALF) and tracheobronchal lymph nodes (TLN) in non-immune piglets upon a challenge with a high dose of APP and to compare the quality of such changes in unprotected piglets with counterparts exhibiting specific immunity mediated by high titers of colostrum-derived APP-specific antibodies and/or a low dose APP infection in the early postnatal period. Challenge with APP resulted in a massive increase in CD8-negative gammadelta T-cells in parallel with a reduction in numbers of CD3-CD8low cells in BALF independent of the type and level of immunity and this seems to be a general phenomenon associated with experimental infection. An increase in B-lymphocyte numbers in TLN was another characteristic feature accompanying APP infection in all experimental groups. In piglets with colostrum-derived APP-specific antibodies, this was associated with higher relative numbers of IgM+CD2+ lymphocytes in TLN, while B-cells with the CD2- surface phenotype apparently expanded in the absence of passive humoral immunity.
Keywords: Respiratory System; bakteriální pneumonie; Sus scrofa; Swine Diseases; podskupiny lymfocytů; imunofenotypizace; Bronchoalveolar Lavage Fluid; zvířata; lymfoidní tkáň; dýchací soustava; Immunophenotyping; Lymphocyte Subsets; Lymphoid Tissue; bronchoalveolární lavážní tekutina; Actinobacillus pleuropneumoniae; nemoci prasat; infekce bakteriemi rodu Actinobacillus; Animals; Pneumonia, Bacterial; Actinobacillus Infections